Video Endoscopic Inguinal Lymphadenectomy: Refi ning surgical technique after ten years experience - Marcos Tobias-Machado; Pericles Rios Auad; Victor Corona; Igor Silva; Oseas de Castro Neves; Eliney Ferreira Faria; Pablo Matos; Alexandre Cesar Santos; Roberto Machado; Aurus Dourado; Hamilton de Campos Zampolli (Global Journal of Cancer Therapy - Peertechz Publications, 2017)
Penile carcinoma is a rare malignant disease with a significantly higher incidence in some areas of underdeveloped countries [1]. Inguinal nodal involvement is found in 20% to 40% of cases at diagnosis and nodal metastasis is an important predictive factor for survival [2,3]. Metastatic penile carcinoma has an extremely poor prognosis, since reported results of systemic therapy have been disappointing, even when improvement is achieved [4-12].